Raising root zone temperature improves plant productivity and metabolites in hydroponic lettuce production - Hayashi, Sota; Levine, Christopher P.; Yu, Wakabayashi; Usui, Mayumi; Yukawa, Atsuyuki; Ohmori, Yoshihiro; Kusano, Miyako; Kobayashi, Makoto; Nishizawa, Tomoko; Kurimoto, Ikusaburo; Kawabata, Saneyuki; Yamori, Wataru (Frontiers in Plant Science, 2024)
While it is commonly understood that air temperature can greatly affect the process of photosynthesis and the growth of higher plants, the impact of root zone temperature (RZT) on plant growth, metabolism, essential elements, as well as key metabolites like chlorophyll and carotenoids, remains an area that necessitates extensive research. Therefore, this study aimed to investigate the impact of raising the RZT on the growth, metabolites, elements, and proteins of red leaf lettuce. Lettuce was hydroponically grown in a plant factory with artificial light at four different air temperatures (17, 22, 27, and 30 °C) and two treatments with different RZTs. The RZT was raised 3°C above the air temperature in one group, while it was not in the other group. Increasing the RZT 3°C above the air temperature improved plant growth and metabolites, including carotenoids, ascorbic acids, and chlorophyll, in all four air temperature treatments. Moreover, raising the RZT increased Mg, K, Fe, Cu, Se, Rb, amino acids, and total soluble proteins in the leaf tissue at all four air temperatures. These results showed that raising the RZT by 3 °C improved plant productivity and the metabolites of the hydroponic lettuce by enhancing nutrient uptake and activating the metabolism in the roots at all four air temperatures.